Strategi Pembelajaran Interaktif Keterampilan Menulis Berita Menggunakan WhatsApp Group - Sofiatin Sofiatin; Rina Nuryani (Journal of Education and Teaching (JET), 2023)
With an average class grade of 86.9 prior to the Covid-19 epidemic, Journalistic Course Studying Achievements (CPMK) by learning news writing techniques was quite ideal. During a pandemic, the course manager expects that CPMK Journalism will continue to function at its best. As a result, academics are working on it and lecturers are putting interactive learning techniques for news writing skills into use via the WhatsApp Group. The one-group, pretest-posttest design of this study combined a descriptive quantitative technique with a pre-experimental design method. This study used interactive learning approaches for news writing skills utilizing the WhatsApp Group. The strategies were taken from Komara (2014). Based on the calculation of the mean (average value), the student received a pretest score of 70.5. Based on the calculation of the mean (average value), the student received a posttest score of 91.5. According to the research questionnaire's findings from ten assertions, students are generally open to using the WhatsApp Group to adopt interactive learning strategies. They also favor using the WhatsApp Group to master interactive news writing tactics.